El geoplano como herramienta didáctica para la resolución gráfica de sistemas de ecuaciones lineales de dos incógnitas, en el primer año de bachillerato general unificado paralelo E, de la unidad educativa anexa a la Universidad Nacional de Loja, ciudad de Loja, periodo 2013 - 2014 - Lima Medina, Ruth Beatriz (2014)
The research had for object the GEOBOARD LIKE A DIDACTIC TOOL FOR THE GRAPHIC RESOLUTION OF SISTEMS OF LINEAR EQUATIONS OF TWO UNKNOWNS, IN THE FIRST YEAR OF GENERAL UNIFIED HIGHER SECONDARY EDUCATION, PARALLEL E OF THE EDUCATIONAL HIGH SCHOOL ANNEXED OF THE NATIONAL UNIVERSITY OF LOJA, LOJA CITY, ACADEMIC PERIOD 2013 – 2014. The objective of the investigative process was proposed of the following way, to apply the geoboard like a didactic tool for the graphic resolution of sistems of linear equations of two unknowns. The research responded to a descriptive and cuasi-experimental pattern (diagnostic). The methods used in this work were: compressive, diagnostic, of patterns, of application and the assessment of the effectiveness of the geoboard like a didactic tool. The principal finding that we met in this research was that the difficulties, lacks or cognitive necessities in the graphic resolution of sistems of linear equations of two unknowns, that can decrease or mitigate with the application of the geoboard like a didactic tool. It responds to a descriptive pattern because we realize a diagnostic of the graphic resolution of sistems of linear equations of two unknowns to determine difficulties, lacks or necessities. Additionally with this information we will propose a cuasi-experimental pattern because deliberately it´ll encourage the graphic resolution of sistems of linear equations of two unknowns in base to the used of the geoboard, perfectly settle in the first year of general unified higher secondary education, parallel E in the determined time and space to apply the alternative proposal and to observe its benefits.The main conclusions to be established was that students know the denotation of a linear equation with one and two unknowns, unknown types of systems of linear equations in the world.